Total Protein Extraction and 2-D Gel Electrophoresis Methods for Burkholderia Species - Velapatiño, Billie (MyJove Corporation, 2013)
The investigation of the intracellular protein levels of bacterial species is of importance to understanding the pathogenic mechanisms of diseases caused by these organisms. Here we describe a procedure for protein extraction from Burkholderia species based on mechanical lysis using glass beads in the presence of ethylenediamine tetraacetic acid and phenylmethylsulfonyl fluoride in phosphate buffered saline. This method can be used for different Burkholderia species, for different growth conditions, and it is likely suitable for the use in proteomic studies of other bacteria. Following protein extraction, a two-dimensional (2-D) gel electrophoresis proteomic technique is described to study global changes in the proteomes of these organisms. This method consists of the separation of proteins according to their isoelectric point by isoelectric focusing in the first dimension, followed by separation on the basis of molecular weight by acrylamide gel electrophoresis in the second dimension. Visualization of separated proteins is carried out by silver staining.